2016
DOI: 10.1007/s12035-016-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

Higher Vulnerability of Menadione-Exposed Cortical Astrocytes of Glutaryl-CoA Dehydrogenase Deficient Mice to Oxidative Stress, Mitochondrial Dysfunction, and Cell Death: Implications for the Neurodegeneration in Glutaric Aciduria Type I

Abstract: Patients affected by glutaric aciduria type I (GA-I) show progressive cortical leukoencephalopathy whose pathogenesis is poorly known. In the present work, we exposed cortical astrocytes of wild-type (Gcdh ) and glutaryl-CoA dehydrogenase knockout (Gcdh ) mice to the oxidative stress inducer menadione and measured mitochondrial bioenergetics, redox homeostasis, and cell viability. Mitochondrial function (MTT and JC1-mitochondrial membrane potential assays), redox homeostasis (DCFH oxidation, nitrate and nitrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…Our human findings agree with the animal data showing inflammation and oxidative stress in the genetic mouse GA‐I model . In this context, it is emphasized that increased pro‐inflammatory cytokines can be related to an excessive production of reactive species, contributing to inflammation .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our human findings agree with the animal data showing inflammation and oxidative stress in the genetic mouse GA‐I model . In this context, it is emphasized that increased pro‐inflammatory cytokines can be related to an excessive production of reactive species, contributing to inflammation .…”
Section: Discussionsupporting
confidence: 90%
“…This may be possibly explained by the fact that L-car has antinitrative properties, preventing nitration of protein tyrosine residues caused by peroxynitrite. 43,44 In this context, it is emphasized that increased pro-inflammatory cytokines can be related to an excessive production of reactive species, contributing to inflammation. 42 We also observed that GA-I patients presented an increase of the pro-inflammatory cytokines IL-6, IL-8, GM-CSF, and TNF-α in plasma, in relation to the control group, indicating a pro-inflammatory state in these patients, that has not been so far evaluated in GA-I patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be also noted that GA1 patients present high levels of proinflammatory cytokines (Guerreiro et al, 2018), as well as marked elevation of various parameters of oxidative stress in plasma and urine (Guerreiro et al, 2015;Mescka et al, 2013). In line with these findings, disturbance of redox homeostasis, glutamatergic neurotransmission, vascular alterations, and inflammatory processes were also observed in cortex and striatum of the GA1 knockout animal model (Amaral et al, 2015;Rodrigues et al, 2016;Wajner et al, 2019). It was also demonstrated that disturbance of redox homeostasis were associated with inflammatory processes induced by quinolinic acid administration in striatum of these mice subjected to dietary lysine overload (Seminotti et al, , 2014.…”
Section: We Investigated Various Markers Of Neurodegeneration and Infsupporting
confidence: 57%
“…If cellular antioxidants fail to scavenge ROS, oxidative damage ensues, leading to cytotoxicity and resulting in protein collapse, enzyme failure and lipid destruction (Lee et al 2012). Furthermore, this could result in the destruction of the neuronal tissue, causing cognitive impairment (Kojima et al 2013;Rodrigues et al 2017).…”
Section: Discussionmentioning
confidence: 99%